Economic and Legal Aspects of Environmental Protection when using Artificial Water Bodies - MUKHLYNINA, Maria Mikhailovna; SHISHANOVA, Elena Ivanovna; NIKIFOROV, Andrey Igorevich; RYAZANOVA, Natalya Yevgenievna; LEBEDEV, Konstantyn Anatolyevich (Journal of Environmental Management and Tourism; Vol 9 No 3 (2018): JEMT Volume IX Issue 3(27) Summer 2018DO - 10.14505//jemt.9.3(27).23, 2018)
The article is dedicated to the economic and legal aspects of environmental protection when using artificial water bodies. It was proved that to improve the efficiency of administrative responsibility for environmental crimes, the size of compensations and penalties should exceed the cost of actions of environmental protection. This will encourage the entities using artificial water bodies to provide advantages to the measures of environmental protection when using artificial water bodies formed within the limits of private land lots. It was offered to distinguish the legally valid and illegal damage to the environment. It was determined that the payment of compensation for the damage to the environment on the base of the special permission of the authorities was not considered a civil and legal liability. The payment of such compensation shall be considered a term for the legal use of the artificial water body by the methods that can be the reason for the damage to the environment.